Upaya Pemerintah Desa Cengkong Dalam Menanggulangi Permasalahan Remaja Putus Sekolah - Mohammad Fikri Akmaludin; Yogi Nugraha; Nadya Putri Saylendra; Fitri Silvia Sofyan (Departement of Mathematics Education, 2024)
The research was motivated by the efforts of the Cengkong village government to overcome the problem of teenagers dropping out of school in Cengkong village. The purpose of conducting this research is to find out what efforts are used by the government in Cengkong village to overcome the problem of teenagers dropping out of school in areas that are under the supervision and responsibility of Cengkong village. As well as describing scientifically and systematically the problem of teenagers dropping out of school. The research used is qualitative research. Namely where this research describes the handling of the problem of teenagers dropping out of school carried out by the Cengkong village. The instruments in this research were observation and interviews. All data obtained and presented in this research are in narrative form. The results of the research that has been carried out show that children in Cengkong village are given easy access to education. There is literacy outreach through the digital library. And if you have already dropped out of school, Cengkong Village provides school facilities to catch up with packages held in the village hall. In this way, the Cengkong village government will not only cope but will also become a solution for those who want to continue their education even though they have already dropped out of school.